COMPLEXITY OF THE TEXT: ABDULLA QODIRIY’S “O‘TGAN KUNLAR” (TRANSLATED INTO ENGLISH BY H. KAMILOV) - Xatamova Sojida Sobir qizi; Jo‘rayev Muhammadrahimxon Murod o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: the study of text complexity has gained significant attention in modern linguistics and discourse analysis, as it encompasses the interaction of linguistic structure, meaning, and cognitive comprehension. Understanding how sentence length, vocabulary, and semantic coherence affect readability is essential not only for education but also for literary translation and comparative stylistics. This research aims to investigate the linguistic complexity of Abdulla Qodiriy’s “O‘tgan kunlar” (translated into English by H. Kamilov) through both quantitative and qualitative analysis. The Flesch–Kincaid readability formula is employed to calculate the difficulty level of the text, while theoretical perspectives by Walter Kintsch (1998) and Arthur C. Graesser (2011) are used to interpret how comprehension depends on linguistic and conceptual integration. The study seeks to demonstrate that classical Uzbek prose, despite translation, retains its semantic richness and syntactic sophistication, reflecting the depth of cultural and emotional expression characteristic of Qodiriy’s literary art.